2011
DOI: 10.1192/bjp.bp.110.085563
|View full text |Cite
|
Sign up to set email alerts
|

Biogenetic explanations and public acceptance of mental illness: Systematic review of population studies

Abstract: Biogenetic causal models are an inappropriate means of reducing rejection of people with mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
248
2
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(285 citation statements)
references
References 56 publications
20
248
2
15
Order By: Relevance
“…The present findings are consistent with the body of research documenting that a biomedical understanding of medical disorders can have negative effects on attitudes (Angermeyer et al 2011;Deacon 2013;Pescosolido et al 2010;Read et al 2013a, b;Speerforck et al 2014). Students who reported heredity among the causes were more pessimistic about recovery and were more sceptical about the usefulness of psychosocial treatments in schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present findings are consistent with the body of research documenting that a biomedical understanding of medical disorders can have negative effects on attitudes (Angermeyer et al 2011;Deacon 2013;Pescosolido et al 2010;Read et al 2013a, b;Speerforck et al 2014). Students who reported heredity among the causes were more pessimistic about recovery and were more sceptical about the usefulness of psychosocial treatments in schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, students who reported biogenetic factors more frequently recommended a medical doctor among the treating professionals. These results support numerous previous findings that the adoption of a biogenetic model of schizophrenia can increase prejudices about incurability of schizophrenia (Angermeyer et al 2011;Read et al 2013b;Kvaale et al 2013) and may led to clinical management of this disorder focused on longterm drug treatments only (Hutton et al 2013). In particular, a review of 17 experimental studies (reviewed by Read et al, 2013a) produced 20 significant findings about causal beliefs and attitudes toward PWS.…”
Section: Discussionsupporting
confidence: 88%
“…Some leading researchers have argued that increased public acceptance of a neurobiological conception of addiction will have important ethical implications for reducing stigma and thereby improving treatment outcomes for addicted individuals (Lebowitz and Ahn, 2012), beliefs that are used to justify neuroscience education campaigns (Vrecko, 2010a). Some empirical studies support the possibility of realising the destigmatising aspirations of addiction neuroscience proponents (Furnham and Rees, 1988;Mehta and Farina, 1997), whereas more recent studies do not (Lam et al, 2005;Angermeyer et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…As Angermeyer et al (2011) have shown, in a number of OECD countries there has been increased public preparedness to accept biogenetic (including neurobiological) explanations of schizophrenia, depression and alcohol dependence. However, trends in the public's acceptance of neurobiological information are not uniform across mental disorders (Schnittker, 2008;Pescosolido et al, 2010;Easter, 2012;Rüsch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Por otro lado, la atribución pública de responsabilidad hacia quien sufre un trastorno mental se establece mayoritariamente cuando se refiere a personas que presentan adicciones, como la dependencia a bebidas alcohólicas, pero con mucha menor frecuencia hacia aquellas personas que sufren depresión o esquizofrenia. 32,33 Otra distinción se ha notado con relación a la eficacia del tratamiento, observándose que la creencia de su efectividad es mayor para el alcoholismo y la depresión, pero menor para la esquizofrenia.…”
unclassified